Review of the Multi-Level Factors Contributing to Fruit and Vegetable Consumption in the US - Zhang, PhD, Qi; Fu, BS, Liuliu (North American Journal of Medicine and Science, 2011)
The consumption of fruits and vegetables (F&V) has a significant protective effect in reducing various cardiometabolic diseases. In recent years, the U.S. government has made a lot of effort to promote F&V consumption through different projects and programs, including the MyPyramid food guidance system supported by the USDA’s Center for Nutrition Policy and Promotion, and the Fruits & Veggies More Matters program (previously called the 5-A-Day for Better Health program), supported by the Centers for Disease Control and Prevention (CDC) and other public and private agencies. However, modest success has been achieved in promoting healthy diets among the American public. Only 40% of Americans eat five or more servings of F&V daily. Using a higher-level F&V consumption standard, less than 10% of American adults meet the MyPyramid recommendations. In order to understand the factors affecting F&V consumption and to summarize the factors from different perspectives into a coherent framework, we look at previous research regarding these various factors and their relationship to F&V consumption. The factors coalesce in three main levels: individual factors, household factors and environmental factors. Individual factors include demographics, dietary habits, lifestyle, health status and sensory appeal; household factors are marital status, number of family members, number of children in the family and parenting practices; and environmental factors consist of food prices, food accessibility and availability, social interaction and seasonal factors. All of these factors may positively or negatively affect F&V consumption among different population groups. Our study will help future researchers and policy makers to gain a more comprehensive understanding of this complex issue and develop more effect ideas for addressing it.